2021
DOI: 10.3390/cells10030522
|View full text |Cite
|
Sign up to set email alerts
|

Role of Heme-Oxygenase-1 in Biology of Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells

Abstract: Heme oxygenase-1 (HO-1, encoded by HMOX1) is a cytoprotective enzyme degrading heme into CO, Fe2+, and biliverdin. HO-1 was demonstrated to affect cardiac differentiation of murine pluripotent stem cells (PSCs), regulate the metabolism of murine adult cardiomyocytes, and influence regeneration of infarcted myocardium in mice. However, the enzyme’s effect on human cardiogenesis and human cardiomyocytes’ electromechanical properties has not been described so far. Thus, this study aimed to investigate the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Thus, to further validate the activity of AC27 in a more complex cellular assembly, we used the human induced pluripotent stem cells (hiPSC)-derived pancreatic organoids. We used a previously described hiPSC line generated from the peripheral blood mononuclear cells with non-integrating Sendai vectors for that purpose [ 54 , 55 ]. The hiPSC differentiation and islet organoid formation depends on transcriptional gene regulation involved in pancreas development and various growth factors and stem cell culture ( Figure S8a ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to further validate the activity of AC27 in a more complex cellular assembly, we used the human induced pluripotent stem cells (hiPSC)-derived pancreatic organoids. We used a previously described hiPSC line generated from the peripheral blood mononuclear cells with non-integrating Sendai vectors for that purpose [ 54 , 55 ]. The hiPSC differentiation and islet organoid formation depends on transcriptional gene regulation involved in pancreas development and various growth factors and stem cell culture ( Figure S8a ).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are required to determine whether HO-1 interacts with other transcription factors including Nrf2 which regulates expression of these genes. A previous study comparing Hmox1 deficient and WT induced pluripotent stem cells reported differential gene expression of over 15 enriched biological process GO Terms [ 57 ]. Our study showed congruence of six biological process terms.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen consumption rate (OCR) in primary hepatocytes was measured using Seahorse Bioscience XFe96 Analyzer (Agilent Technologies, Santa Clara, CA, USA) according to our protocol described previously 86 , 87 . Briefly, 1 × 10 5 of live hepatocytes (determined by the trypan blue staining) were plated into Seahorse XFe96-well plates directly after isolation.…”
Section: Methodsmentioning
confidence: 99%